Nasal Dorsum Reduction Simultaneous to Orthognathic Surgery: A Proof-of-Concept Report - Foraster, Joan Birbe (Facial Plastic Surgery, 2021)
This report describes a technique to reduce nasal dorsum excess simultaneously to orthognathic surgery (OS) through a Le Fort I osteotomy. It avoids the need to change from endonasal intubation to intraoral intubation. It also eliminates the need to open the dorsum, preserving the integrity of the triangular cartilages at the nasal dorsum keystone area, avoiding iatrogenic nasal dorsum deformities. A sample of five patients referred for OS who also sought improvement of their nasal aesthetics was selected to implement the technique. The aim of this proof-of-concept study was to evaluate the clinical outcome of simultaneous OS and nasal dorsum reduction. The following measurements were used to evaluate the procedure: patient satisfaction with a visual analog scale, photographic assessment, additional operative time, and complications related to the procedure. The average patient age was 23 years (range: 19–32 years). Three patients were women and two were men. In all patients, a high degree of patient satisfaction was observed with the aesthetic result of the nose and OS. No undesirable side effects or surgical complications occurred in any case. Total surgery time was increased by an average of 25 minutes. Nasal dorsum reduction through a Le Fort I approach during OS is a reliable and effective method to reduce nasal dorsum excess in patients seeking simultaneous OS and rhinoplasty.
Keywords: rhinoplasty; preservation rhinoplasty; orthognathic surgery; Le Fort I